Digital Technology and Marketing Development Model for UMKM COMET CP BOJONG - Ginanjar, Yayat; Rindiyani, Fitri; Awaliah, Sofia Adisti Novarini; Apriyanti, Windi (Journal of Bussines Management Basic, 2026)
This study analyzes the development model of Comet UMKM in CP. Bojong Village through the utilization of digital technology and digital marketing strategies. The research aims to assess the extent of technology implementation in production, promotion, and product distribution, as well as to identify challenges and opportunities in enhancing business competitiveness. This study applies a descriptive qualitative approach with data collected through direct observation and in-depth interviews with business actors. The findings indicate that Comet UMKM has initiated the use of social media and marketplace platforms, yet data management and content marketing strategies have not been fully optimized. Limited digital literacy, inadequate promotional planning, and resource constraints remain major barriers. Therefore, strengthening digital marketing management and advancing technology adoption are urgently needed to expand market reach and improve business performance.